KEMANDIRIAN DAN KEDISIPLINAN KERJA SISWA KELAS XI SMK NEGERI 5 PADANG DALAM PRAKTIK PEMESINAN” - Permana, Kaesarion Rahman; Purwantono, Purwantono; Nabawi, Rahmat Azis; Fauza, Anna Niska (Jurnal Vokasi Mekanika (VoMek), 2024)
The Fourth Industrial Revolution presents difficulties that all countries must face head-on by using technology extensively in all aspects of daily life. Education is meant to provide students withithe knowledge they need toisucceed in various aspects of life. Answering the problems faced now, especially in the industrial field, SMK Negeri 5 padang plays a good role in shaping the characteriof students, in accordance with the vision of SMK Negeri 5 padang is to become an educational produce reliable human resources in the industrial era. Based on observations in machining practice research, it was found that space facilities, machining tools, and practice hours still need more attention to improve student skills. One example is the low level of student independence and discipline. This study aimsito examine the relationship between independence and discipline of grade XI students with machining practice at SMK Negeri 5 Padang. Based on the study, it was found significant relationship between independence and discipline in machining practice, as seen from the test results conducted during the study. A total of 33 xi gradeistudents of the Department ofpMechanical Engineering participated in the study in the January-June 2023/2024 academic year. The results showed a significant relationship between independence and discipline of class XI students at SMK N 5 . This is shownifrom the results of the correlation test with the value of r count> r table (0.567> 0.334) therefore the hypothesis in the study can be accepted.